A formação continuada mediada por tecnologia: Programa de Ações Formativas em Teatro e Artes Integradas - Reginaldo dos Santos (2022)
The present research introduces the Program of Formative Actions in Theatre and Integrated Arts (Programa de Ações Formativas em Teatro e Artes Integradas – PAFT), carried out through the use of technological devices. The research departed from the social presence of acting basic education teachers, through the practice of traditional and theatrical games over the internet, in both synchronous and asynchronous classes. Most of the teachers who were the subjects of the research had no background in art. They all teach in the early years of elementary school (1st to 5th grade). A training course in theater and integrated arts was carried out with twelve different groups, by means of distance learning using the Zoom Virtual Conferencing Software. The meetings were recorded, and the material was used for the analysis, considerations, and in the development of the research. The theoretical field deals with social representations, continuing education, construction of knowledge, aesthetic experience, digital technology, reflective practice of the teacher, social presence, and the teaching of traditional and theatrical games. Among the possibilities addressed, it is concluded that the social presence of PAFT participants could be expanded from interactive proposals that sought to provoke the use of body language in the virtual environment. The games adapted to the virtual context and tried out during the research proved to be very satisfactory alternatives in the recreational and theatrical fields, surprisingly promoting teaching and learning relationships between the participants. Therefore, the construction of a vast field of possibilities in the teaching of contemporary theatrical language begins, and this thesis proves that it can be mediated by video conference technology.